2015
DOI: 10.1183/09031936.00092614
|View full text |Cite
|
Sign up to set email alerts
|

Statement on smoking cessation in COPD and other pulmonary diseases and in smokers with comorbidities who find it difficult to quit

Abstract: Chronic obstructive pulmonary disease (COPD), lung cancer, asthma and pulmonary tuberculosis are common pulmonary diseases that are caused or worsened by tobacco smoking. Growing observational evidence suggests that symptoms and prognosis of these conditions improve upon smoking cessation. Despite increasing numbers of (small) randomised controlled trials suggesting intensive smoking cessation treatments work in people with pulmonary diseases many patients are not given specific advice on the benefits or refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
138
0
26

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(166 citation statements)
references
References 143 publications
2
138
0
26
Order By: Relevance
“…Tobacco smoke contains over 60 known carcinogens [4]. The relative risk of lung cancer development is estimated to be 10-to 30-fold in longterm smokers when compared with never smokers [5].…”
Section: Original Researchmentioning
confidence: 99%
“…Tobacco smoke contains over 60 known carcinogens [4]. The relative risk of lung cancer development is estimated to be 10-to 30-fold in longterm smokers when compared with never smokers [5].…”
Section: Original Researchmentioning
confidence: 99%
“…This is supported by previous research which showed that COPD smokers have 'difficulty in finding the right time to quit' (Eklund et al, 2012, p.1) and that smokers from disadvantaged communities find it difficult to cope without a cigarette (Bancroft, Wiltshire, Parry, & Amos, 2003;Stead, MacAskill, MacKintosh, Reece, & Eadie, 2001); and struggle to overcome barriers to quit (Copeland, 2003). It is therefore possible that the computer-tailored feedback reports did not adequately cater to the needs of these smokers, by providing the intensive help necessary as advocated by the recent statement on smoking cessation interventions for those with pulmonary disease (Jiménez-Ruiz, et al, 2015). A longer term intensive tailored approach might improve the success of this intervention.…”
Section: Discussionmentioning
confidence: 91%
“…Although the impact of smoking on respiratory diseases has been well documented, with evidence for increased risk of complications, increased hospital time, accelerated decline in lung function and death (Burchfiel, Marcus, Curb, & Maclean, 1995); many people continue to smoke after diagnosis (Baron, 2003). Current evidence suggests that disease progression and prognosis can be improved, with smokers benefitting from a reduction in patient symptoms like chronic cough, loss of breadth and wheezing and improved response to medication, if smokers with respiratory conditions quit smoking (Jiménez-Ruiz, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, COPD can be para-, meta-, and post-tuberculosis process [1]- [4]. Both diseases have similar risk factors: smoking, low socio-economic status of the individual and the violation of the immune defense [5]- [7]. A related aspect of the above pathogenetic nosology is the development of destructive changes in the pulmonary parenchyma, caused, in particular, a metabolic disorder due to exposure to tobacco metalloproteinases or virulence factors Mycobacterium tuberculosis [2] [5] [8].…”
Section: Purposementioning
confidence: 99%